MANIPULATIVE STRATEGIES OF GASLIGHTING AND CONSTANT DISAPPOINTMENT IN THE COMMUNICATION OF NEGATIVE CHARACTERS IN THE NOVEL OF A. MANZONI “BETROTHED” - Okhrimenko , Valeria (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The manipulative strategies of "gaslighting" and "constant disappointment" in the communication of negative characters in A. Manzoni’s novel "Betrothed" are analyzed. It has been established that implementation tactics of "gaslighting" are the imposition of value orientations with overemphasis and suggestions, while implementation tactics of "constant disappointment" are devaluation, distancing, emotional pressure, threats. The perlocutionary effect of using manipulative strategies "gaslighting" and "constant disappointment" is the resultant force of influence of mentioned tactics. Each of these tactics has specific linguistic markers of expression; however, all the tactics are interrelated. The manipulator’s speech is characterized by using of prescriptive-directive speech acts that introduce values imposed by the manipulator, prohibitive-directive speech acts that realize value reorientation of the victim, suggestives that accentuate imposed values, and menasives being their functional purpose intimidating the victim and destabilizing her psycho-emotional sphere. Language means of expression the tactics of manipulative strategies "gaslighting" and "constant disappointment" are characterized by the following features: exaggerated negative evaluation of the victim "una rea, un’indegna, una scomunicata"; verbalization of neglecting the victim: "veniva corrisposta con uno sguardo sprezzante" "corrisposta con una noncuranza manifesta"; lexical units to indicate the physical isolation of the victim in a closed space: "clausura... stretta e intera; monastero", verbalization of minimizing communication with the victim and ignoring her "l’abbandono in cui era lasiata", "o non attaccava, o veniva corrisposta con uno sguardo distratto"; lexical units of emotional semantics to indicate the emotional alienation of the manipulator and ignoring the victim’s desire for emotional connection: "seri, tristi, burberi", "insisteva, e tentava di famigliarrizzarsi; lexical units of emotional semantics to denote insecurity, oppression, fear of the victim: "rimaneva poi umiliata, e sempre più afflitta, il terrore"; "sommessamente e tremando"; "uno sguardo tra atterrito e supplichevole". The produced perlocutionary effect as a result of manipulative strategies is explained by the victim’s desire to avoid cognitive dissonance in her mind, which is caused by conflicting feelings, emotions, values. Verbal and non-verbal behavior of the victim of manipulations shows her helplessness and passive role in communication. A. Manzoni’s use of synonymous series and tropes creates a semantic field of tension that reflects, on the one hand, the confrontation between manipulators and the victim, and on the other, cognitive dissonance in the victim’s consciousness. Мanzoni created synonymous series for the designation of the victim of manipulations that reflect doom «la nostra infelice», «povera innocentina», «sventurata» and hyperbolized negative evaluation of the victim by manipulators: «una rea», «un’indegna», «scomunicata». The other synonymous series are used for the designation of causation of will imposed by manipulator: «irrevocabilmente stabilita», «necessità fatale», «vocazione impostale» and for the designation of isolation of the victim: «prigionia – carceriera – guardiana – clausura – monastero». A.Manzoni uses metaphor «prigionia» and comparison «clausura era stretta e intera, come nel monastero» for the designation of Gertrude’s parents’ castle. Asyndeton is used by A. Manzoni, on the one hand, in the speech of manipulator for suggesting, on the other hand, to indicate cognitive dissonance in the mind of the victim overwhelmed by conflicting feelings. Gradation, on the one hand, is used in the speech of manipulators to increase pressure on the victim: «seri, tristi, burberi», on the other hand, to increase the emotional tension and state of despair of the victim: «un altro gastigo oscuro, indeterminato, e quindi più spaventoso». Antithesis is the trope par excellence for describing the confrontation between manipulators and the victims and is used: to denote asymmetric communication between manipulators and the victim: «una gran confidenza – l’abbandono»; to indicate cognitive dissonance in the victim’s mind, which is caused by conflicting feelings, emotions and values: «il rimorso del fallo, e una tenerezza fantastica di divozione; l’orgoglio amareggiato e irritato». The use of antithesis with the second component being part of gradation produces reinforcing effect: «quel fantasma – seri, freddi, minacciosi». The main antithesis is the contradiction between what is desired and what is real, which the victim of manipulation finally realizes: «brillanti fantasie d’una volta – circostanze reali». __________ References: • Bigunova, O. «Ilokutyvni tsili ta perlokutyvnyj efect movlennjevogo actu skhvalennja (na materiali anglomovnogo literaturnogo dyskursu)». Naukovyj visnyk Mizhnarodnogo gumanitarnogo universytetu 38 (2019): 55–59. • Gumenjuk, Y. Psykhologija vplyvu (Ternopil’: Ekonomichna dumka, 2003), 304. • Zirka,V. V. «Movna paradygma manipuljatyvnoji gry v reklami» (avtoref. dys. d-ra filol. nauk, Kyjiv, 2005), 34. • Kovalenko,A. M. «Movni zasoby realizatsiji manipuljatyvnogo vplyvu v suchasnykh anglomovnykh ZMI». Naukovyj visnyk Mizhnarodnogo gumanitarnogo universytetu 38 (2019): 214–218. • Kozak,S. V. «Komunikatyvni strategiji jak zasib manipuljatyvnogo vplyvu v anglomovnykh pres-relizakh». Naukovi zapysky Natsional’nogo universytetu «Ostroz’ka akademija». Serija «Filologichna» 23 (2012): 68–70. • Levchenko,L. О. «Psykhologichni osoblyvosti dijal’nosti zasobiv masovoji informatsiji». Liudyna i polityka 2 (2001): 103-108. • Petrenko, V. Osoblyvosti vyznachennja politychnoji movy «Politychnyj menedzhment» 2 (2007): 16-24. • Rizun,V. V., Nepyjvoda, N. F., Kornejev, V. M. Lingvistyka vplyvu (Kyjiv, 2005), 148. • Ruda,O. G. Movne pytannja jak objekt manipuljatyvnykh strategij u suchasnomu ukrajins’komu politychnomu dyskursi (Kyjiv, 2012), 232. • Slovnyk psykhologichnykh terminiv (Kyjiv, Ukrajina, 2015), https://nuph.edu.ua/slovnik-psihologichnih-terminiv/ (accessed: 01.23). • Dijk, A. What is a Political Discourse Analysis? «Political linguistics» 11 (1997): 11-52. • Dunmire, Political Discourse Analysis: Exploring the Language of Politics and the Politics of Language «Language and Linguistics Compass» 6 (11) (2012), 735-751. • Festinger, A Theory of Cognitive Dissonance (Stanford: Stanford University Press, 1962), 291. • L’Acchiappabugiardi (Padova, Italia, 2019), https://agentievenditori.it/pdf/Acchiappabugiardi.pdf (accessed: 11.01.23). • Panicucci, Manipolazione mentale: i profili penali tra dogmatica e politica criminale (Pisa: Università di Pisa, 2018), 297. • Samir, Salama, R. «Struttura e narratore ne I Promessi Sposi di Alessandro Manzoni» Romanica Silesiana 17 (1) (2020): 138-150. https://doi.org/10.31261/RS.2020.17.11 (accessed 23.04.23). • Smascherare chi mente (Lugano, Svizzera, 2013), https://www.donadelli.eu/smascherare-chi-mente.html (accessed: 23.01.23). • Taylor, Brainwashing: the science of thought control (Oxford: Oxford University Press, 2004), 213. • Tecniche di manipolazione psicologica. La mente meravigliosa (Roma, Italia, 2018), https://lamenteemeravigliosa.it/tecniche-di-manipolazione-psicologica/ (accessed: 11.06.22). • Vascotto, «Gli indici comportamentali della menzogna: analisi verbale e non verbale» (Trieste, Italia, 2019), https://arts.units.it/retrieve/e2913fdd-6ad5-f688-e053-3705fe0a67e0/Documento%20di%20tesi.pdf. • Manzoni, I promessi sposi (Milano: Mondadori, 1985), 816.